PASAL-PASAL NUSYUZ ISTRI DALAM KOMPILASI HUKUM ISLAM DAN KEKERASAN DALAM RUMAH TANGGA - Ristian, Ika (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
ABSTRACT Marriage is one thing that has broad consequences in the legal relationship between husband and wife. With marriage there arises a right and obligation. A wife who does not carry out her obligations in fiqh munakahat is called nushuz. In the Compilation of Islamic Law it is explicitly stated that the act of cheating is only done by a wife, and in this case the husband has the right to treat his wife who are cheating in the Compilation of Islamic Law explained that this cheating act of the wife can abort the income he gets from her husband. The rights of the husband are considered to be able to cause domestic violence experienced by the wife. Things like this become a problem in married life. Based on the background and subject matter above, the researchers' objectives are To find out the problematics of the concept of wife nusyuz and husband's rights in the Compilation of Islamic Law (KHI) and the treatment of husbands who have the potential to become acts of Domestic Violence (Domestic Violence) and To describe the relevance of the concept of wife nushuz according to the Compilation of Islamic Law (KHI) with Law No. 23 of 2004 concerning the Elimination of Domestic Violence. This research is a literature research that sourced on the primary legal material, compilation of Islamic Law (Kompilasi Hukum Islam/ KHI) and Law No. 23 of 2004 about the removal of household violence, as well as secondary law material in the form of books, documents , etc. Then this research was then analyzed using content analytical techniques. This study uses a type of grounded theory design. Then this study was analyzed using content analysis techniques and carried out a moving analysis from descriptive to theoretical level that is connecting concepts based on data with concepts in the literature. Based on the results of the study, it can be concluded that in understanding the concept of nusyuz is often wrong, it is not always the wife who refuses intimacy and the wife who leaves the household with permission from the husband is the wife of nushuz. Compilation of Islamic Law has no binding law, the position of Compilation of Islamic Law under Law No. 23 of 2004 concerning the Elimination of Domestic Violence. For the relevance of the Compilation of Islamic Law and Law No. 23 of 2004 concerning the Elimination of Domestic Violence, it is forbidden to commit violence. Keyword: Husband's rights; Islamic law Compilation; Law of the domestic voilence; Wife's nusyuz. ABSTRAK Perkawinan merupakan salah satu hal yang mempunyai akibat luas dalam hubungan hukum antara suami istri. Dengan adanya perkawinan maka timbullah suatu hak dan kewajiban. Seorang istri yang tidak melaksankan kewajibanya dalam fiqh munakahat disebut dengan perilaku nusyuz. Dalam Kompilasi Hukum Islam disebutkan secara tegas bahwa tindakan nusyuz hanya dilakukan oleh seorang istri, dan dalam hal ini suami mempunyai hak untuk memperlakukan istrinya yang nusyuz dalam Kompilasi Hukum Islam dijelaskan bahwa tindakan nusyuz istri ini dapat menggugurkan nafkah yang ia peroleh dari suaminya. Hak suami disinilah dianggap dapat menimbulkan terjadinya kekerasan dalam rumah tangga yang dialami oleh istri. Hal seperti ini menjadi permasalahan dalam kehidupan berumah tangga. Berdasarkan latar belakang dan pokok masalah di atas maka yang menjadi tujuan peneliti adalah Untuk mengetahui problematika konsep nusyuz istri dan hak suami dalam Kompilasi Hukum Islam (KHI) dan perlakuan suami yang berpotensi menjadi tindak Kekerasan dalam Rumah Tangga (KDRT) dan mendeskripsikan relevansi konsep nusyuz istri menurut Kompilasi Hukum Islam (KHI) dengan Undang-Undang No. 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga. Penelitian ini merupakan penelitian kepustakaan yang bersumber pada sumber data hukum primer yakni Kompilasi Hukum Islam (KHI) dan Undang-Undang No. 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga, serta sumber data sekunder yang berupa buku-buku, dokumen-dokumen. Penelitian ini menggunakan jenis desain grounded theory. Kemudian penelitian ini di analisis menggunakan teknik content analisis dan melakukan moving analysis from descriptive to theoretical level yaitu menghubungkan konsep berdasarkan data dengan konsep-konsep yang ada dalam literatur. Berdasarkan hasil penelitian, dapat disimpulkan bahwa dalam pemahaman konsep nusyuz istri sering kali salah, tidak selamanya istri yang melakukan penolakan berhubungan intim dan istri yang meninggalkan rumah tangga seiizin suami adalah istri nusyuz. Kompilasi Hukum Islam tidak mempunyai hukum yang mengikat, Kedudukan Kompilasi Hukum Islam di bawah Undang-undang No. 23 Tahun 2004 tentang Penghapusan Kekerasan dalam Rumah Tangga. Untuk relevansi antara Kompilasi Hukum Islam dan Undang-Undang No. 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga sama-sama melarang adanya tindak Kekerasan. Kata Kunci: Hak Suami; Kompilasi Hukum Islam; Nusyuz Istri; Undang-Undang Kekerasan Dalam Rumah Tangga.